PENGARUH SCARCITY MESSAGE DAN SHOPPING ENJOYMENT TERHADAP IMPULSE BUYING MELALUI FEAR OF MISSING OUT (FoMO) SEBAGAI VARIABEL INTERVENING STUDI PADA KONSUMEN LIVE STREAMING SHOPEE DI KOTA PADANG - Rahmandani, Suci Alifah; Rahmidani, Rose (Penerbit Lafadz Jaya, 2025)
Competition between marketplaces is increasing over time, due to the increasing number of marketplace platforms present in Indonesia. This study aims to examine the effect of scarcity messages and shopping enjoyment on impulse buying through fear of missing out (FoMO) as an intervening variable on Shopee live streaming consumers. This study was conducted with an unknown population of Padang City residents and a sample of 130 respondents who had made impulsive purchases during live streaming on Shopee with a non-probability sampling technique, especially purposive sampling. Data analysis in the study using SEM-PLS, showed that scarcity messages and fear of missing out (FoMO) did not have a direct effect on impulse buying, while shopping enjoyment had a direct and positive effect on impulse buying. Furthermore, scarcity messages and shopping enjoyment had a direct and positive effect on fear of missing out (FoMO). The indirect effect shows that scarcity messages and shopping enjoyment did not affect impulse buying through fear of missing out (FoMO).